2000
DOI: 10.1111/j.1346-8138.2000.tb02141.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of HLA‐DR and ‐DQ Genes in Japanese Patients with Bullous Pemphigoid

Abstract: Bullous pemphigoid (BP), an autoimmune skin disease of the elderly, is mediated by autoantibodies that bind to hemidesmosomes of epidermal basal cells. This study investigated BP-associated HLA-DR and -DQ genes among Japanese patients. We analyzed HLA-DR and -DQ genes among 23 Japanese BP patients based on the polymerase chain reaction-restriction fragment length polymorphism. Eighteen of these 23 patients (78%) carried at least one allele of HLA-DRB1*04 or DRB1*1101, with significant increases in HLA-DRB1*04 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 38 publications
1
39
1
4
Order By: Relevance
“…The pathomechanism in the production of the autoantibodies remains to be clarified, although several drug-induced cases suggested the involvement of immune dysregulation by such drugs [10, 11, 12]. Okazaki et al [13]studied the HLA genotypes in Japanese BP patients and found a higher incidence of DRB1 *0403, *0406, DQB1 *0302 haplotype, as well as the individual alleles DRB1 *1101 and DQB1 *0302. Our present patient showed different HLA genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The pathomechanism in the production of the autoantibodies remains to be clarified, although several drug-induced cases suggested the involvement of immune dysregulation by such drugs [10, 11, 12]. Okazaki et al [13]studied the HLA genotypes in Japanese BP patients and found a higher incidence of DRB1 *0403, *0406, DQB1 *0302 haplotype, as well as the individual alleles DRB1 *1101 and DQB1 *0302. Our present patient showed different HLA genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In more detail, pemphigus vulgaris, an ASBD with Dsg 3 as the target antigen (Amagai et al, 1991), was found to be associated with HLA-DRW4 in a Jewish cohort, with HLA-DQw1 and -DQw3 polymorphisms in Ashkenazi Jews, HLA-DRB1*04 and DRB1*1401 in Iranian patients, HLA-DRB1*0402 haplotypes in Venezuelan patients, HLA-DQB1*0503, -B*1507 or -DRB1*1405 in Japanese patients, as well as HLA-B38 and HLA-Bw55 in an American cohort (Park et al, 1979;Szafer et al, 1987;Miyagawa et al, 1999Miyagawa et al, , 2002Lee et al, 2006;Saenz-Cantele et al, 2007;Shams et al, 2009). For bullous pemphigoid (BP), an ASBD with antibodies directed against hemidesmosomal proteins termed BP180 (type XVII collagen, COL17) and BP230 (Stanley et al, 1981(Stanley et al, , 1988Diaz et al, 1990), major histocompatibility complex (MHC) association studies have also not been conclusive (Delgado et al, 1996;Okazaki et al, 2000). In 29 patients with epidermolysis bullosa acquisita (EBA) and 5 patients with bullous lupus erythematodes, an association with HLA-DR2 has been described (Gammon et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Em um outro estudo simultâneo com a população japonesa foram analisados os genes HLA-DR e -DQ em 23 casos com PB, e os pesquisadores obtiveram um aumento significativo de HLA-DRB1*04 (*0403, *0406)/DQA1*0301/DQB1*0302 e DRB1*1101/DQA1*0505/DQB1*0302 haplótipos, bem como os alelos individuais DRB1*1101 e DQB1*0302 (corrigido p < 0,05 para cada comparação), quando conferidos com os controles [75] .…”
Section: Sistema Hla Nas Populaçõesunclassified
“…Apesar de estudos anteriores [74,75] não comprovarem a associação com alelos classe I em outras populações, na brasileira foi possível evidenciar essa característica. Portanto, é a primeira vez que se demonstrou a correlação de um HLA classe I com o penfigoide bolhoso.…”
Section: Associação Hla E a População Brasileiraunclassified
See 1 more Smart Citation